Risk analysis of cardiovascular mortality after gastric cancer diagnosis: a large population-based study - Qiang Zhao; Qiaohong Zhou; Jiayue Dong; Qiang Tong (Frontiers in Cardiovascular Medicine)
BackgroundThe increasing prevalence of cardiovascular mortality is becoming a significant worry for individuals who have survived cancer. The aim of this study is to investigate the dynamic trend of cardiovascular death in patients with gastric cancer (GC) and identify the risk factors associated with cardiovascular disease (CVD)-specific mortality in non-metastatic GC patients.MethodsIn the present study, 29,324 eligible patients diagnosed with primary GC were collected from the Surveillance, Epidemiology, and End Results (SEER) database. Standardized mortality ratios (SMRs) adjusted by age, gender, calendar year, and race were calculated. Fine-Gray's competing risk models were taken to identify the prognostic factors of cardiovascular death in GC patients.ResultsThere were 1083 (5.2%) cardiovascular deaths among 20,857 patients with local/regional GC, and 76 (0.9%) cardiovascular deaths among 8,467 patients with metastatic GC. The SMRs of CVD-specific mortality continuously increased since the 1975s throughout the 2015s. The competing risk models showed that age (>75 years vs. 0–50 years, HR: 6.602, 95% CI: 4.356–10.006), T stage (T4 vs. T1, HR:0.524, 95% CI: 0.370–0.741), N stage (N3 vs. N0, HR: 0.557, 95% CI: 0.343–0.903), surgery (Yes vs. No, HR: 0.551, 95% CI: 0.461–0.659), and radiotherapy (Yes vs. No, HR: 1.011, 95% CI: 1.011–1.437) were predictive of CVD-specific mortality. Furthermore, based on the results of the competing risk analyses, a nomogram was constructed to predict the probability of CVD-specific mortality for local/regional GC patients.ConclusionOur study demonstrated the dynamic trend of cardiovascular death in GC patients, and identified prognostic risk predictors, highlighting the importance cardio-oncology teams in offering comprehensive care and long-term follow-up for GC patients.